Regression of prostate tumors after intravenous administration of lactoferrin-bearing polypropylenimine dendriplexes encoding TNF-α, TRAIL, and interleukin-12 - Najla Altwaijry; Sukrut Somani; John A. Parkinson; Rothwelle J. Tate; Patricia Keating; Monika Warzecha; Graeme R. Mackenzie; Hing Y. Leung; Christine Dufès (Taylor & Francis Group, 2018)
The possibility of using gene therapy for the treatment of prostate cancer is limited by the lack of intravenously administered delivery systems able to safely and selectively deliver therapeutic genes to tumors. Given that lactoferrin (Lf) receptors are overexpressed on prostate cancer cells, we hypothesized that the conjugation of Lf to generation 3-diaminobutyric polypropylenimine dendrimer would improve its transfection and therapeutic efficacy in prostate cancer cells. In this study, we demonstrated that the intravenous administration of Lf-bearing DAB dendriplexes encoding TNFα resulted in the complete suppression of 70% of PC-3 and 50% of DU145 tumors over one month. Treatment with DAB-Lf dendriplex encoding TRAIL led to tumor suppression of 40% of PC-3 tumors and 20% of DU145 tumors. The treatment was well tolerated by the animals. Lf-bearing generation 3-polypropylenimine dendrimer is therefore a highly promising delivery system for non-viral gene therapy of prostate cancer.